Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jof7090708
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in CAPA, a Possible Fungal Super-Infection

Abstract: The occurrence of pulmonary fungal superinfection due to Aspergillus spp. in patients with COVID-19 is a well-described complication associated with significant morbidity and mortality. This can be related to a directed effect of the virus and to the immunosuppressive role of the therapies administered for the disease. Here, we describe the first case of pulmonary infection due to Mucorales occurring in a patient with a concomitant diagnosis of COVID-19-associated pulmonary aspergillosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…False positive results of GM in serum have previously been seen in patients receiving beta-lactam treatment [15] , however our patient had finished the course of piperacillin/tazobactam 3 days before blood sampling for GM was done. Reports of mucormycosis cases with positive GM have been published previously [ 16 , 17 ] , as well as reports of CAM cases with concomitant aspergillosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…False positive results of GM in serum have previously been seen in patients receiving beta-lactam treatment [15] , however our patient had finished the course of piperacillin/tazobactam 3 days before blood sampling for GM was done. Reports of mucormycosis cases with positive GM have been published previously [ 16 , 17 ] , as well as reports of CAM cases with concomitant aspergillosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with active infection caused by pathogens (e.g., SARS CoV-2) an increased incidence of fungal infection (e.g. aspergillosis [11] , cryptococcosis, candidiasis [12] , [13] , Coccidioides [14] , Geotrichum [15] Fusarium [16] , Mucorales [17] Mucorales+Aspergillus [18] Pneumocystosis [19] , Mucormycosis, Histoplasmosis) was detected [20] . Finally it has been observed that excessive use of steroid drugs make patients susceptible to mucormycosis which can occur anytime during hospitalization or after hospitalization [21] .…”
Section: Introductionmentioning
confidence: 99%